PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA DENGAN ORIENTASI PASAR SEBAGAI VARIABEL MODERASI (Survey pada Salon Kecantikan di Kecamatan Banjarsari Kota Surakarta) - Setyaningsih SU Edi Wibowo (RESEARCH FAIR UNISRI, 2018)
This study aims to analyses role of market orientation as moderating variable of the effectentrepreneurship orientationon on business performace. This study using sample 62 entrepreneurof the industry beautiful salon at Banjarsari district Surakarta. To test hypothesis using regressionanalysis with absolute difference test. Conclusion of test results shows that the direct effect ofentrepreneurship orientation on business performance is significant. Other findings indicate thatmarket orientation moderates the effect of entrepreneurship orientation on business performance,indicated by increase in R value of 19,6% and Adj.R2 of 15,1% means that the higher interactionbetween entrepreneurship orientation and market orientation will affect the improvement ofbusiness performance. Implication, entrepreneur of the industry beautiful salon should not onlyhave entrepreneurship orientation but should be supported with higher market orientation so thatbusiness performance will be more optimal.Keywords : entrepreneurship orientation, market orientation, business performace